Wewenang Notaris dalam Pembuatan Akta Notaril terhadap Tanah Hak Guna Bangunan di atas Tanah Hak Milik untuk Pembangunan Hotel - Anak Agung Made Wahyu Purwanta; I Nyoman Sumardika; Ni Ketut Sri Astiti (Jurnal Konstruksi Hukum, 2020)
The building right can be given on land with ownership rights and the granting of rights to build on land with ownership rights is made with the deed of the official land deed maker (hereinafter referred to as the PPAT Deed) instead of the deed made before a Notary (hereinafter referred to as the Notary Deed), where the Deed The PPAT will be registered at the land office. A notary in the view of society is considered an official, a place for someone to obtain reliable legal advice, a place for making strong legal documents in a legal process that will be carried out, especially in making a deed of agreement for hotel development. This study aims to determine the authority of the notary in making a notarial deed of land use rights on land for hotel development, second, how is the existence of a notarial deed in granting building use rights over land of ownership for hotel construction. The type of this research is normative legal research, data sources based on primary legal materials, secondary legal materials and tertiary legal materials. The approach used in this research is a statutory approach. The technique of collecting legal data is literature study. The results in the research are the task of the notary office is to formulate the wishes or actions of the parties into an authentic deed, so that to carry out its duties a notary must adhere to the applicable regulations, secondly the existence of a notary deed in granting development rights over land of ownership rights for hotel development, the existence of a notary deed in granting the right to build on land owned for hotel construction has a positive character because there are very important requirements, namely an evidence of ownership of land, as well as the building on it in a formal or written form of a certificate